Sedentary behavior and health concepts, assessments, and interventions - Owen, Neville; Zhu, Weimo 1955- (Champaign, IL Human Kinetics, 2017)
From office jobs and long commutes to passive entertainment like television and video games, humans are sitting more than ever. Though lack of exercise has major health consequences, researchers are now examining the additional and widespread health risk of the simple act of sitting for extended periods. With research from leading scientists, Sedentary Behavior and Health: Concepts, Assessments, and Interventions presents evidence on sedentary behavior, its apparent health risks, and suggestions on measuring and altering this behavior. The highly respected international author team provides an interdisciplinary review of current research, examining scientific, public health, and broader social questions about the implications of sedentary behavior. These topics include humans' physiological predispositions, exacerbation of current health conditions like obesity and diabetes, and the design and ergonomics of offices and chairs. To examine the many facets of this developing area of study, Sedentary Behavior and Health is divided into five parts: "Sedentary Behavior Concepts and Context" reviews the physiology of sedentary behavior, investigating current habits from the perspectives of evolution, industrial engineering, and design; "Sedentary Behavior and Health" explores the relationship between sedentary behavior and several major chronic diseases, including obesity, cardiovascular disease, and low-back pain; "Measuring and Analyzing Sedentary Behavior" explains research methods for understanding and measuring sedentary behavior in order to recognize patterns and design interventions; "Sedentary Behavior and Subpopulations" covers issues, risks, and behaviors in groups such as children, working adults, older adults, and minorities; "Changing Sedentary Behavior" provides methods and recommendations for improvement with environmental, social, community, worksite, and technology-based interventions. Included in this groundbreaking text are learning objectives, key concepts, and study questions to focus attention on key issues and reinforce concepts. Reviews of the literature in the field are presented, many with comparisons in table form, to provide the full scope of research. Sidebars throughout the text apply theoretical concepts to real-world scenarios. Inactivity is mismatched with many aspects of humans' genetic makeup. While it is becoming the new norm, the consequences of this behavior are emerging as a public health threat. Sedentary Behavior and Health will serve as a key reference for the rapidly emerging research area of sedentary behavior.
Part I. Sedentary Behavior Concepts and Context -- Chapter 1. Emergence of Research on Sedentary Behavior and Health / Neville Owen ; Contemporary Sedentary Behavior Research and Concepts ; Sedentary Behavior and Health ; Sedentary Research Agenda ; Sedentary Behavior Research Priorities ; Summary -- Chapter 2. Gravity, Sitting, and Health / Joan Vernikos ; Gravity and Spaceflight ; Head Down Bed Rest Studies ; Gravity Deprivation Syndrome ; Health Consequences of Prolonged Sitting and Gravity ; Perceiving Gravity ; Gravity Intervention Design and Implementation ; Summary -- Chapter 3. Physiological Effects of Reducing and Breaking Up Sitting Time / David W. Dunstan, Bethany J. Howard, Audrey Bergouignan, Bronwyn A. Kingwell, and Neville Owen ; Methodological Considerations for Studies of Sedentary Behavior ; Metabolic Effects of Reduced Sitting and the Postprandial State ; Cardio Metabolic Effects Following Exposure to Reduced Sitting ; Cardiometabolic Effects of Repeated-Day Exposure to Reduced Sitting ; Public Health and Clinical Guidelines ; Summary -- Chapter 4. Rethinking the Chair and Sitting / Galen Cranz ; Problems with Sitting in Chairs ; Chair Designer Response ; Postural Education ; Summary -- Chapter 5. Children and Screen Time / Jorge A. Banda and Thomas N. Robinson ; Screen Time Exposure ; Mobile Devices and Screen Time Changes ; Influences on Media Use ; Screen Time and Body Weight ; Screen Time and Cardiometabolic Risk Factors ; Screen Time, Physical Activity, and Cardiorespiratory Fitness ; Screen Time and Dietary Habits ; Experimental Studies of Reducing Screen Time ; Summary -- Part II. Sedentary Behavior and Health -- Chapter 6. Economics of Sedentary Occupations / Kenneth A. Glover ; Economic Sectors ; Economics of Inactivity ; Worksite Health Promotion ; Regulation and Innovation ; Choice Architecture ; Summary -- Chapter 7. Sedentary Behavior and Obesity / Michael L. Power ; Role of Fat ; Adipose Tissue and Endocrine Function ; Mismatch Paradigm ; Obesity and Inflammation ; Central Versus Peripheral Obesity ; Sex Differences in Fat Storage and Mobilization ; Vitamin D, Adipose Tissue, and Sedentary Behavior ; Obesity Prevalence ; Summary -- Chapter 8. Sedentary Behavior and Incident Diabetes / Carl J. Caspersen and G. Darlene Thomas ; Diabetes Statistics ; Key Risk Factors ; Epidemiological Diabetes Research ; Research Limitations ; Six Criteria to Assess a Causal Inference for Sedentary Behavior and Diabetes ; Summary -- Chapter 9. Sedentary Behavior and Cardiovascular Disease / Edward Archer, Enrique G. Artero, and Steven N. Blair ; Cardiovascular Diseases ; Occupational Physical Activity and CVD ; Physical Activity and CVD ; Summary -- Chapter 10. Sedentary Behavior and Cancer / Brigid M. Lynch and Christine M. Friedenreich ; Cancer Epidemiology ; Key Risk Factors ; Sedentary Behavior and Cancer Research ; Sedentary Behavior and Cancer Survivorship ; Proposed Biological Mechanisms ; Summary -- Chapter 11. Sedentary Behavior and Low Back Pain / Marco S. Boscolo and Weimo Zhu ; Low Back Pain and Its Impact ; Spine Anatomy ; Spine Stability ; Known Risk Factors of Low Back Pain ; Relationship Between Low Back Pain and Sedentary Behavior ; Prevention of Low Back Pain ; Summary -- Chapter 12. Sedentary Behavior and Psychological Well-Being / Stuart J.H. Biddle and Stephan Bandelow ; Sedentary Behavior and Depression ; Sedentary Behavior and Cognitive Functioning ; Sedentary Behavior and Health-Related Quality of Life ; Summary -- Part III. Measuring and Analyzing Sedentary Behavior -- Chapter 13. Assessing Sedentary Behavior Using Questionnaires / Barbara E. Ainsworth, Alberto Floŕez Pregonero, and Fabien Rivier̀e ; Key Components of Questionnaires ; Measurement Principles of Questionnaires ; Practical Guidelines ; Summary -- Chapter 14. Assessing Sedentary Behavior Using Motion Sensors / Kong Y. Chen and Richard P. Troiano ; Key Components of Motion Sensors ; Measurement Principles of Motion Transducers ; Accelerometers ; Practical Guidelines ; Potential of Raw Accelerometer Data ; Summary -- Chapter 15. Assessing Sedentary Behavior Using Physiological Sensors / David Bassett and Dinesh John ; Key Components of Physiological Sensors ; Measurement Principles of Physiological Sensors ; Practical Guidelines ; Summary -- Chapter 16. Assessing Sedentary Behavior Using New Technology ; Dinesh John and Stephen Intille ; Existing Technology for Measuring Sedentary Behavior ; Sedentary Behavior Measurement Goals ; Improvements and Emerging Technology for Measuring Sedentary Behavior ; Data Collection, Storage, and Open Source Processing ; Summary -- Chapter 17. Critical Measurement and Research Issues in Analyzing Sedentary Behavior / Weimo Zhu ; Sedentary Behavior Data Characteristics ; Challenges and Solutions in the Analysis of Sedentary Behavior Data ; Summary -- Part IV. Sedentary Behavior and Subpopulations -- Chapter 18. Sedentary Behavior in Children / Gregory J. Welk and Youngwon Kim ; Measures of Sedentary Behavior in Youth ; Health Effects of Sedentary Behavior in Youth ; Epidemiology of Sedentary Behavior in Youth ; Differences in Sedentary Behavior by Age and Gender ; Social and Cultural Differences in Sedentary Behavior in Youth ; Correlates of Youth Sedentary Behavior ; Patterns of Youth Physical Activity and Sedentary Behavior ; Intervention Approaches for Sedentary Behavior in Youth ; Summary -- Chapter 19. Occupational Sedentary Behavior in Adults / Wendy J. Brown ; Most Sedentary Occupations ; Characteristics of Sitting at Work ; Health Effects of Occupational Sitting ; Changing Sitting at Work to Improve Health Outcomes ; Summary -- Chapter 20. Sedentary Behavior of Older Adults / Jorge A. Banda, Sandra J. Winter, and Abby C. King ; Measuring Sedentary Behavior in Older Adults ; Health and Functional Outcomes of Sedentary Behavior ; Putative Drivers of Sedentary Behavior ; Possible Contexts of Sedentary Behavior ; Interventions Aimed at Reducing Sedentary Behavior ; Summary -- Chapter 21. Sedentary Behavior in Racial/Ethnic Minority Groups / Melicia C. Whitt-Glover and Tyrone G. Ceaser ; Statistics ; Correlates of Sedentary Behavior ; Interventions to Reduce Sedentary Behavior in Racial/Ethnic Minorities ; Summary -- Part V. Changing Sedentary Behavior -- Chapter 22. Psychological and Behavior-Based Interventions / Kevin Moran and John P. Elder ; Theories of Reasoned Action and Planned Behavior ; Social Cognitive Theory ; Health Belief Model ; Transtheoretical Model ; Operant Conditioning, Contingency Management and Positivistic Models ; Socioecological Models ; Summary -- Chapter 23. Environment and Policy Interventions / Jordan A. Carlson and James F. Sallis ; Comprehensive Multi-Level Approaches ; Evaluating Environment and Policy Interventions ; Integrating Environment and Policy Interventions with Other Approaches ; Practical Guidelines ; Summary -- Chapter 24. Sedentary Behavior and Worksite Interventions / Nicolaas P. Pronk ; Characteristics of Worksite Interventions ; Applications of Worksite Interventions ; Practical Guidelines ; Summary -- Chapter 25. Community Based Interventions / Adrian Bauman and Josephine Y. Chau ; Framework for Assessing Sedentary Behavior-Reducing Interventions ; Evaluating Community-Based Interventions ; Practical Guidelines ; Summary -- Chapter 26. Ergonomics of Redesigning Sitting / John B. Shea ; Characteristics and Impact of Chair Designs and Positional Behaviors ; Applications of Sitting Redesign ; Practical Guidelines ; Summary -- Chapter 27. Emerging Communication Systems to Curb Physical Inactivity / Dolores Albarracin, Vera Liao, Jessica Yi, and Cheng Zhai ; Determinants of Exposure and Attitude ; Determinants of Attitude and Behavior Change ; Information Systems ; Summary.
Includes bibliographical references
Keywords: Sedentary behavior